2014
DOI: 10.1039/c4em00126e
|View full text |Cite
|
Sign up to set email alerts
|

Difference in production routes of water-soluble organic carbon in PM2.5observed during non-biomass and biomass burning periods in Gwangju, Korea

Abstract: 4 h integrated PM2.5 samples were collected from an urban site of Gwangju, Korea, for five days and analyzed for organic carbon and elemental carbon (OC and EC), total water-soluble OC (WSOC), hydrophilic and hydrophobic WSOC fractions (WSOCHPI and WSOCHPO), oxalate, and inorganic ionic species (sodium (Na(+)), ammonium (NH4(+)), potassium (K(+)), calcium (Ca(2+)), magnesium (Mg(2+)), chloride (Cl(-)), nitrate (NO3(-)), and sulfate (SO4(2-))) to investigate the possible sources of water-soluble organic aerosol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 60 publications
0
12
1
1
Order By: Relevance
“…Biomass burning (BB) is a significant primary source of WSOC Zhang et al, 2010;Du et al, 2014;Yu et al, 2014;Kuang et al, 2015). WSOC is often considered a proxy for secondary organic aerosols (SOA) due to its highly oxidized nature (Weber et al, 2007;Park et al, 2013a;Yu et al, 2014;Kuang et al, 2015). In addition to BB emissions and SOA, traffic emissions are known primary sources of particulate WSOC (Ruellan and Cachier, 2001;Ho et al, 2006;Saarikoski et al, 2008;Cho and Park, 2013;Park et al, 2013a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biomass burning (BB) is a significant primary source of WSOC Zhang et al, 2010;Du et al, 2014;Yu et al, 2014;Kuang et al, 2015). WSOC is often considered a proxy for secondary organic aerosols (SOA) due to its highly oxidized nature (Weber et al, 2007;Park et al, 2013a;Yu et al, 2014;Kuang et al, 2015). In addition to BB emissions and SOA, traffic emissions are known primary sources of particulate WSOC (Ruellan and Cachier, 2001;Ho et al, 2006;Saarikoski et al, 2008;Cho and Park, 2013;Park et al, 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…It is emitted directly from combustion sources, and is formed by the gas-to-particle conversion processes (Seinfeld and Pandis, 2006). Biomass burning (BB) is a significant primary source of WSOC Zhang et al, 2010;Du et al, 2014;Yu et al, 2014;Kuang et al, 2015). WSOC is often considered a proxy for secondary organic aerosols (SOA) due to its highly oxidized nature (Weber et al, 2007;Park et al, 2013a;Yu et al, 2014;Kuang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…따라서 본 연구에서는 도시지역 에서 약 1년 동안 PM 2.5 를 측정하여 WSOC의 상당한 부분을 차지하고 있는 HULIS의 일반적 화학 특성과 생성과정을 조사하였다. (Park et al, 2013a;Park and Shin, 2013;Jeong et al, 2011 Yu et al, 2014;Park et al, 2013a Park et al, 2013a;Park and Cho, 2011;Kondo et al, 2007;. …”
Section: 현재까지 수행된 대기 중의 총 Wsoc 또는 Hulisunclassified
“…7. Yu et al (2014) reported that the slope of the equation for the regression between BC 370nm and BC 880nm is 0.95 for the non-BB period and 1.29 for the BB period, which correspond to BC 880nm /BC 370nm values of 1.05 (non-BB) and 0.77 (BB) here. As seen in Fig.…”
Section: Diurnal Variation Of Cn Concentration Gmd Bc Mass Concentrmentioning
confidence: 99%
“…Previous studies using aethalometer measurements have suggested that certain organic aerosol components such as aromatic organic species of wood smoke or BB aerosols have enhanced UV absorption at 370 nm, relative to that at 880 nm (Jeong et al, 2004;Park et al, 2006;Sandradewi et al, 2008;Kumar et al, 2011;Wang et al, 2011;Yu et al, 2014). Therefore, the ratio between BC concentrations measured at wavelengths of 880 nm (BC 880nm ) and 370 nm (BC 370nm ), also known as UVBC, as well as the Delta-C value (BC 370nm −BC 880nm ) were calculated and plotted in Fig.…”
Section: Diurnal Variation Of Cn Concentration Gmd Bc Mass Concentrmentioning
confidence: 99%